AGING AND LOSS MINIMIZATION: THE ROLE OF PROBABILITY IN DECISION-MAKING. (11th November 2018) - Best, R; Freund, A
Abstract: Older adults are stereotypically considered to be risk-averse compared to younger age groups, although meta-analyses on age and gain-loss framing on risky choices have not found empirical evidence for age differences in risk taking. The current study extends the investigation of age differences in risk preference by including analyses on the effect of the probability of a risky option on choices in gain vs. loss situations. Participants (N = 130 adults aged 19 to 80 years) chose between a certain option and a risky option of varying probability in gain- and loss-framed gambles with actual monetary outcomes. Only younger adults displayed an overall framing effect. Younger and older adults responded differently to probability fluctuations depending on the framing condition. Older adults were more likely to choose the risky option as the likelihood of avoiding a larger loss increased and as the likelihood of a larger gain decreased. Younger adults responded with the opposite pattern: they were more likely to choose the risky option as the likelihood of a larger gain increased and as the likelihood of avoiding a (slightly) larger loss decreased. Results suggest that older adults are more willing to select a risky option when it increases the likelihood that larger losses be avoided, whereas younger adults are more willing to select a risky option when it allows for slightly larger gains. This finding supports expectations based on theoretical accounts of goal orientation shifting away from securing gains in younger adulthood towards maintenance and avoiding losses in older adulthood.